2021
DOI: 10.3168/jds.2021-20262
|View full text |Cite
|
Sign up to set email alerts
|

Integration of statistical inferences and machine learning algorithms for prediction of metritis cure in dairy cows

Abstract: The study's objectives were to identify cow-level and environmental factors associated with metritis cure to predict metritis cure using traditional statistics and machine learning algorithms. The data set used was from a previous study comparing the efficacy of different therapies and self-cure for metritis. Metritis was defined as fetid, watery, reddish-brownish discharge, with or without fever. Cure was defined as an absence of metritis signs 12 d after diagnosis. Cows were randomly allocated to receive a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…On the other hand, studies evaluating metabolomic changes in the uterus and related reproductive tract components during the first weeks postpartum and their association with metritis are only now emerging and need further exploration [16]. Our approach in the current study was supported by a premise that vaginal discharge, a sample that is relatively simpler and less invasive to collect than uterine fluid [16], could still be satisfactory to identify biomarkers for metritis development and its cure that could serve as data entry points to advance current predictive models for a metritis cure [18,20] and shed light on potential mechanisms of disease pathogenesis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…On the other hand, studies evaluating metabolomic changes in the uterus and related reproductive tract components during the first weeks postpartum and their association with metritis are only now emerging and need further exploration [16]. Our approach in the current study was supported by a premise that vaginal discharge, a sample that is relatively simpler and less invasive to collect than uterine fluid [16], could still be satisfactory to identify biomarkers for metritis development and its cure that could serve as data entry points to advance current predictive models for a metritis cure [18,20] and shed light on potential mechanisms of disease pathogenesis.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have reported the associations of minerals or metabolites with immune function and metritis development [17,18]. Also, studies revealed that predictive models using cows' sensor data [19] or machine learning algorithms [20] to predict a metritis cure might help improve the judicious use of antibiotics. However, studies characterizing the vaginal-uterine metabolome and potential biomarkers associated with the risk of metritis development and its cure remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the similarity in the uterine microbiome of cows with metritis that cured and those with clinical cure failure on day 5, it is possible that other mechanisms related to immune response play a major role in clinical cure. Studies have reported that cows diagnosed with metritis and pyrexia (rectal temperature ≥ 39.5 °C) were less likely to cure compared with cows with metritis without pyrexia 5,27 . Furthermore, concurrent injuries and inflammation were associated with reduced a risk of achieving clinical cure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to optimize animal reproduction, it is crucial to associate management strategies that can promote better efficiency in reproductive animal management. In this regard, there are already several studies proposing the use of AAM systems and exploring machine learning algorithms to enhance the prediction of health and fertility disorders in dairy cows [ 51 , 52 , 53 ]. A previous study has also shown that routinely collected farm data and milk production records on the test day are valuable for predicting the success of insemination in dairy cows [ 54 ].…”
Section: Discussionmentioning
confidence: 99%